2017
DOI: 10.5114/aoms.2015.55270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic pain in the elderly Polish population – results of the PolSenior study

Abstract: IntroductionPain is the most common complaint of elderly people. In Poland, no large studies on the prevalence of chronic pain in the elderly were conducted until recently.Material and methodsThe study was a part of the PolSenior project, a cross-sectional multidisciplinary study on ageing of the Polish population, and included a randomly selected group of 716 people aged 55–59 years, and 4979 people over 65 years. The survey was conducted through a standardized questionnaire. An evaluation of pain occurrence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
4
22
0
1
Order By: Relevance
“…This study showed that musculoskeletal and rheumatic disease disorders were the most common causes of chronic pain in the elderly; this finding was consistent with the results of previous studies [13,17,18]. Osteoarthritis, a common joint disorder in the world, is one of the most common causes of pain and disability in the geriatric population [18][19][20][21]. The greatest risk factor for osteoarthritis is old age, and other risk factors are joint injury, obesity, genetics, anatomical factors, and female sex [19,22].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that musculoskeletal and rheumatic disease disorders were the most common causes of chronic pain in the elderly; this finding was consistent with the results of previous studies [13,17,18]. Osteoarthritis, a common joint disorder in the world, is one of the most common causes of pain and disability in the geriatric population [18][19][20][21]. The greatest risk factor for osteoarthritis is old age, and other risk factors are joint injury, obesity, genetics, anatomical factors, and female sex [19,22].…”
Section: Discussionsupporting
confidence: 93%
“…Chronic pain was seen in 57.7% of our patients and seen more common in female ones. PolSenior study conducted in Poland among older adults showed that 41.8% of community dwelling individuals older than 80 years suffered from chronic pain (19). Blyth et al (20) found that the prevalance of chronic pain was 55% for those aged above 85; which is similar to our finding.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, the studies among adult populations show that the prevalence of chronic pain is higher in all countries [30]. Musculoskeletal system pain is being studied in a wide range from non-specific pain to pain as a result of an underlying pathological condition such as chronic renal failure [31].…”
Section: Discussionmentioning
confidence: 97%